Mucopolysaccharidosis type I - Clinical and genetic characteristics of Romanian patients - Alkhzouz Camelia; Lazea Cecilia; Miclea Diana; Asavoaie Carmen; Nascu Ioana; Pop Tudor; Grigorescu-Sido Paula (Romanian Journal of Laboratory Medicine, 2020)
Background: Mucopolysaccharidosis type I (MPS I) is an autosomal recessive lysosomal storage disorder caused by a deficiency of α-L-iduronidase (IDUA), which leads to the accumulation of partially digested glycosaminoglycans (dermatan sulfate and heparan sulfate) in the lysosomes and induces multisystemic alteration. Hurler (severe), Scheie (mild), and Hurler/Scheie (intermediate) syndromes are clinical subtypes of MPS-I. To date, more than 290 IDUA mutations have been reported. The purpose of this study was to present the clinical and genetic characteristics of Romanian MPS I syndrome patients and their genotype-phenotype correlation.